JARINGAN KOMUNIKASI DALAM MENINGKATKAN PRODUKTIVITAS PELAPAK (STUDI KASUS PADA KOMUNITAS BUKALAPAK WILAYAH JAKARTA) - Retno Dyah Kusumastuti; Agung Wicaksono; Anjang Priliantini (BPSDMP Kominfo Manado, 2019)
In the last five years, the number of SMEs in Indonesia has continued to increase. However, only 4.9% made use of digital access as a sales medium, either through social media or e-commerce. In 2017, the number of SMEs going online increase to 8%, and is targeted to increase in 2018 by the Minister of Cooperatives and SMEs of the Republic of Indonesia. Increasing e-commerce is a challenge for Bukalapak. To continue to maintain its exixtance, Bukalapak formed the ‘Komunitas Pelapak’ as a communication network between ‘pelapak’ (seller) in each region. This community allows pelapak to share strategies to increase productivity. This study aims to describe the communication network of ‘Komunitas Pelapak’ in the Jakarta area and analyze it’s role in improving the productivity of pelapak in the community. This research method is qualitative descriptive using a case study spproach. The study, which used in-depth interview techniques with members of the Komunitas Bukalapak Jakarta area, found that within the Bukalapak community in Jakarta, there were four (4) individuals who were chosen by members of the community. The four individuals constitute opinion leaders who are active in providing information and motivation to other community members through social media channels, the WhatsApp Group of the Bukalapak community, and offline activities such as ‘kopdar’ and social activities. By communicating with information and motivation in every community activity, it can increase enthusiasm and innovation for the products and also the sales method. This will ultimately increase the productivity of community members in doing business in the world of e-commerce.